A Risk Assessment Method for Trench Excavations - Lee, Sun Chai*; Chen, Shen En (Cafet Innova Technical Society, 2015)
Many earthwork excavations are being made for pipeline and other utility installation each year. However, frequent slope failures occur in this type of earthwork resulted in many casualties and property losses. These site accidents often occur because contractors consider these excavations as temporary earthwork that would not warrant regular engineering analyses for the slopes. An engineering stability analysis of slopes is considered to be too tedious to conduct. This paper describes a study to provide a quick and easy method to analyze the safety of trenches and excavations which can be used for immediate on-site evaluation. This method uses the direct correlation between the minimum factor of safety and their soil parameters through multiple regressions. However, the use of these equations requires site personnel to have some experience in geotechnical engineering.